Implications of the Collar Sign in Incompletely Occluded Aneurysms after Pipeline Embolization Device Implantation: A Follow-Up Study - Gomez-Paz, S. (AJNR Am J Neuroradiol, 2020)
BACKGROUND AND PURPOSE: The angiographic collar sign has been recently described in patients with incompletely occluded aneurysms after Pipeline Embolization Device implantation. The long-term implications of this sign are unknown. We report angiographic outcomes of patients with the collar sign with follow-up of up to 45 months and the implications of this angiographic finding. MATERIALS AND METHODS: We performed a retrospective review of a prospectively maintained data base of patients who underwent Pipeline Embolization Device implantation for an intracranial aneurysm at our institution between January 2014 and December 2016. We included patients with a collar sign at the initial follow-up angiogram after Pipeline Embolization Device implantation. RESULTS: A total of 198 patients with 285 aneurysms were screened for the collar sign on initial and subsequent follow-up angiograms. There were 226 aneurysms (79.3%) with complete occlusion at the first follow-up. Of 59 incompletely occluded aneurysms, 19 (32.2%) aneurysms in 17 patients were found to have a collar sign on the first angiographic follow-up (median, 6 months; range, 4.2–7.2). Ten (52.6%) aneurysms underwent retreatment with a second Pipeline Embolization Device, which resulted in aneurysm occlusion in 1 (10%) patient. There were only 3 (15.8%) aneurysms with complete occlusion at the last follow-up, 2 (10.5%) of which had a single Pipeline Embolization Device implantation and another single (5.3%) aneurysm with a second Pipeline Embolization Device implantation. CONCLUSIONS: A collar sign on the initial angiogram after Pipeline Embolization Device placement is a predictor of poor aneurysm occlusion. Because the occlusion rates remain equally low regardless of retreatment in patients with a collar sign, radiologic follow-up may be more appropriate than retreatment.